Experimental Setup of Driver Behavior on Road Darkness Level - Md Yusof, N.; Karjanto, J.; Hassan, M.Z.; Sulaiman, S.; Mustaffa, N. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Most of the previous research on the road darkness effect in Malaysia focused on traffic flow characteristics such as traffic speed and its density. Only limited efforts have been made to assess the road darkness effect on driver behaviours. In this paper, an experimental setup is explained to study driver behaviours when approaching parked or slow- moving vehicles during nighttime. A single-carriageway was selected to conduct the study. The road lighting will be controlled to be switched on or switched off during the experiment. Three obstacles in the shape of a motorcycle, car, and lorry will be used to simulate the parked or slow-moving vehicle. The experimental setup is designed to collect driver behaviour data including the reaction time taken for breaking or slowing down when approaching the obstacle, the distance between the car and the obstacle, the speed of the car and its trajectory. This experimental setup is expected to be used in a study that investigates the effect of dark roads on driver behavior.